Kill the heroes : a Charlie Henry mystery - Thurlo, David (Thurlo, David. Charlie Henry mysteries., 2017)
"Charlie Henry, co-owner of a pawnshop and Iraq war veteran, has, for the most part, settled into his somewhat quieter life in Albuquerque. He is invited to attend the dedication of a memorial in a park, where he, other local heroes, and first responders are to be honored for their military accomplishments and dedication to the community. But trouble always seems to follow Charlie. When gunshots ring out, barely missing Charlie and hitting the man next to him, it's clear that a dangerous madman is on the loose. More shots are fired, and two more veterans are injured. Charlie thinks he might have been the target and looks around for the shooter. The crowd is in a panic, and he's unable to spot the gunman. Charlie tries to help the man who took the first hits, Nathan Whitaker, a decorated former Army helicopter pilot who has been badly wounded. No one is dead, at least not yet. But Charlie vows to find the evil person who would attack American heroes--he refuses to go down without a fight and knows that the perpetrator will soon learn that he has messed with the wrong man"--